Clinical trial landscape of gene therapy for retinal degenerative diseases: an analysis based on the Trialtrove database - Shizhou Cheng; Chuyun Xing; Zijian Chen; Shu Zhang; Wanghao Chen (Stem Cell Research & Therapy)
Abstract Gene therapy has changed the way retinal degenerative diseases are explored and treated. Analyzing past and ongoing clinical trials using gene therapy for retinal degenerative diseases will provide important insight into academic, medical, and other communities. This study retrospectively analyzed 209 clinical trials in the Trialtrove database initiated before 2025.